2019
DOI: 10.1097/ccm.0000000000003768
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Studies in the ICU: A Systematic Review*

Abstract: Objectives: Cost-effectiveness analyses are increasingly used to aid decisions about resource allocation in healthcare; this practice is slow to translate into critical care. We sought to identify and summarize original cost-effectiveness studies presenting cost per quality-adjusted life year, incremental cost-effectiveness ratios, or cost per life-year ratios for treatments used in ICUs. Design: We conducted a systematic search of the English-language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 105 publications
0
25
0
1
Order By: Relevance
“…Wilcox and colleagues recently summarised economic evaluations of interventions in critical care and despite searching the literature from 1993 to 2018, identified just 20 evaluations of sepsis interventions, compared to 46 evaluations of sepsis interventions in the current review [14]. Our review differs from that of Wilcox and colleagues in that we did not restrict our search by year of publication, language, or location of critically ill patients (Wilcox and colleagues limited their review to the ICU setting).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilcox and colleagues recently summarised economic evaluations of interventions in critical care and despite searching the literature from 1993 to 2018, identified just 20 evaluations of sepsis interventions, compared to 46 evaluations of sepsis interventions in the current review [14]. Our review differs from that of Wilcox and colleagues in that we did not restrict our search by year of publication, language, or location of critically ill patients (Wilcox and colleagues limited their review to the ICU setting).…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, numerous other interventions for the treatment of sepsis have been evaluated. Wilcox and colleagues recently published a systematic review of the cost effectiveness literature in critical care medicine; however, their review was limited to intensive care interventions and English language publications [14]. Given the global burden of sepsis, we conducted a contemporary systematic review of economic evaluations of interventions for sepsis management in critically ill adult patients, including interventions delivered outside of the intensive care setting (such as in the emergency department) and articles published in languages other than English.…”
Section: Introductionmentioning
confidence: 99%
“…The literature currently has a paucity of health economic evaluations, illustrating the importance of E-PROSPECT. 40 strengths and limitations Some aspects of our methodology have potential limitations. First, the time horizon is relatively short, with no outpatient follow-up (only reporting in-hospital outcomes).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ICUs reduce the mortality rate in a cost-effective manner, and cost-effectiveness analyses are a strong argument in resource allocation for intensive care medicine ( 8 ). Nevertheless, a relatively new publication concluded that “despite critical care being a significant healthcare cost burden, there is a paucity of studies evaluating its cost effectiveness” ( 9 ).…”
Section: Cost-effectiveness Analysesmentioning
confidence: 99%